Studi Perbandingan Larangan Poligami dalam Hukum Perkawinan Belanda dan Implikasinya terhadap Kebebasan Beragama - Muhammad Daffa Nurramadhan Munir (Program Studi Hukum Keluarga Islam (HKI) dan bekerjasama dengan Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2026)
Polygamy is one of the contemporary issues in marriage law that continues to spark debate, particularly regarding its relationship with religious freedom and the protection of human rights. Differences in how countries regulate polygamy reflect the legal frameworks followed by each legal system. This article aims to analyze the prohibition of polygamy in Dutch marriage law and its impact on religious freedom, comparing it with the regulation of polygamy in Indonesia. This study uses a normative legal research method with a legislative and comparative law approach. The results show that Indonesia applies the principle of monogamy but allows limited polygamy through strict legal mechanisms as a compromise between religious values and the protection of women's rights. In contrast, the Netherlands completely prohibits polygamy as a result of the principles of secularism and gender equality in family law. These differences influence how each country interprets religious freedom in the context of family law. This article concludes that both conditional restrictions and total bans on polygamy have different legal and social implications, so that the regulation of polygamy should ideally consider the balance between religious freedom, the protection of human rights, and public order.